Epithelial cell identity in hyperplastic precursors of breast cancer - Coradini, Danila (Chin J Cancer, 2015)
INTRODUCTION: In the adult human breast, hyperplastic enlarged lobular unit (HELU) and atypical ductal hyperplasia (ADH) are two common abnormalities that frequently coexist with ductal carcinoma in situ (DCIS). For this reason, they have been proposed as the early steps in a biological continuum toward breast cancer. METHODS: We investigated in silico the expression of 369 genes experimentally recognized as involved in establishing and maintaining epithelial cell identity and mammary gland remodeling, in HELUs or ADHs with respect to the corresponding patient-matched normal tissue. RESULTS: Despite the common luminal origin, HELUs and ADHs proved to be characterized by distinct gene profiles that overlap for 5 genes only. While HELUs were associated with the overexpression of progesterone receptor (PGR), ADHs were characterized by the overexpression of estrogen receptor 1 (ESR1) coupled with the overexpression of some proliferation-associated genes. CONCLUSIONS: This unexpected finding contradicts the notion that in differentiated luminal cells the expression of estrogen receptor (ER) is dissociated from cell proliferation and suggests that the establishing of an ER-dependent signaling is able to sustain cell proliferation in an autocrine manner as an early event in tumor initiation. Although clinical evidence indicates that only a fraction of HELUs and ADHs evolve to invasive cancer, present findings warn that exposure to synthetic progestins, frequently administered as hormone-replacement therapy, and estrogens, when abnormally produced by adipose cells and persistently present in the stroma surrounding the mammary gland, may cause these hyperplastic lesions.